The endonuclease activity of MCPIP1 controls the neoplastic transformation of epithelial cells via the c-Met/CD44 axis - Paulina Marona; Rafał Myrczek; Iga Piasecka; Judyta Gorka; Oliwia Kwapisz; Ewelina Pospiech; Janusz Rys; Jolanta Jura; Katarzyna Miekus (Cell Communication and Signaling)
Abstract The RNase activity of MCPIP1 is essential for regulating cellular homeostasis, proliferation, and tumorigenesis. Our study elucidates the effects of downregulation of MCPIP1 expression and an RNase-inactivating mutation (D141N) on normal epithelial kidney cells, indicating that MCPIP1 expression is a key factor that suppresses neoplastic transformation. We observed that either expression downregulation or mutation of MCPIP1 significantly increased its clonogenicity and altered the expression of cancer stem cell (CSC) markers and factors involved in epithelial-to-mesenchymal transition (EMT). In vivo studies demonstrated that MCPIP1 inactivation in normal epithelial cells leads to significant tumor formation and increased c-Myc phosphorylation, indicating enhanced cell proliferation. Proteomic analysis of mouse plasma revealed increased secretion of cancer-related proteins (CXCL13, CXCL16, and MMP2) in the MCPIP1-mutant group. Additionally, we revealed that MCPIP1 RNase activity regulates the expression of the stemness markers CD44 and CD133 and the phosphorylation of the c-Met receptor in tumor tissue samples. Mechanistically, via coimmunoprecipitation analysis, we found that the RNase activity of MCPIP1 controls CD44 expression and, consequently, that a strong interaction between CD44 and c-Met leads to c-Met activation. This regulation was confirmed in patient samples, in which increased CD44 expression correlated with ccRCC progression. These findings highlight the critical role of MCPIP1 RNase activity in modulating the c-Met/CD44 axis, thereby influencing stemness and tumorigenesis.